The Influence of Folklore on the Cultivated Albanian Music of the XX Century - Bizhga, Denis (European Journal of Multidisciplinary Studies, 2020)
Folklore is one of the components and transmitters of a nation’s national identity and its spiritual heritage. The great folkloric wealth of Albanian people shows its antiquity and creative genius. As the first creation of folklore, it is the basis for the creation and continuous functioning of other cultivated arts, such as: music, literature, choreography or other visual arts. Albanian folklore also represents a vital, early, stable and rich tradition. It is not a memory of the past, but it is alive and full of life and day by day it comes and is practiced articulated emotionally, developing, enriching and growing together with the Albanian people themselves, despite the many changes that are noticed in the realities of Albanian folklore in general. Through folklore, our people over the centuries manifested outstanding talent, spiritual expressive potential, great promotional skills. Albanian folk music tradition is generally an oral tradition based on the memory of the people; she did not feel the need for writing because she was born, spread and selected to live word of mouth and generation after generation, adapting to the needs and requirements of life.